Assessment of suitability of vine shoots for hemicellulosic oligosaccharides production through aqueous processing. (July 2016) - Dávila, Izaskun; Gordobil, Oihana; Labidi, Jalel; Gullón, Patricia
Graphical abstract: Highlights: Oligosaccharides obtention from vine shoots using autohydrolysis. Spent solids enriched in cellulose and lignin can be used in further processes. Characterization of hemicellulosic oligosaccharides using HPLC, HPSEC, FTIR and TGA. Aqueous processing of vine shoots is proposed as a first step of a biomass refinery. Revalorization of vine shoots using friendly environmental technologies. Abstract: Vine shoots were subjected to non-isothermal aqueous processing. A range of severities ( S 0 ) from 3.20 to 4.65 was assayed and their effects in terms of solubilization, composition, molar mass distribution, structural characterization and thermal stability of the liquors were studied using HPLC, HPSEC, TGA and FTIR. The spent solids were characterized by HPLC and FTIR. When autohydrolysis was carried out at S 0  = 4.01, the substrate solubilization achieved a 38.7% of the raw material and 83.1% of the initial xylan was converted into xylooligosaccharides (XOS). The amount of TOS (total oligosaccharides) in the hydrolysates was 28.4 g/L while the other non volatile compounds (ONVC) were 0.08 g/g NVC. The spent solid from the treatment at S 0  = 4.01 was composed about 90% of cellulose and lignin. Therefore, it can be concluded that autohydrolysis is a suitable pretreatment of vine shoots such as a first stage of a biomass refinery.